Aneuploidy rates and morphokinetic parameters of embryos cultured in distinct culture media: a sibling oocyte study. Issue 2 (13th November 2021) - Quinn, Molly M; Marsh, Philip; Ribeiro, Salustiano; Simbulan, Rhodel K; Hickman, Cristina; Berntsen, Jørgen; Rosen, Mitchell P
Abstract: STUDY QUESTION: Do embryos from sibling oocytes assigned to distinct single-step media culture systems demonstrate differences in early embryo development, morphokinectics or aneuploidy rates? SUMMARY ANSWER: Embryo quality, morphokinetic parameters and aneuploidy rates from trophectoderm biopsy were similar between sibling embryos cultured in distinct media systems from the time of gamete isolation. WHAT IS KNOWN ALREADY: Studies on the effect of commercially available embryo culture media systems have demonstrated inconsistent impact on human embryonic development, morphokinetics, aneuploidy rates and clinical outcomes. In addition, these studies have been primarily randomized at the level of the embryo or the patient to culture media. STUDY DESIGN, SIZE, DURATION: Prospective sibling oocyte cohort derived from 200 subjects undergoing IVF at a tertiary academic medical center between February 2018 and November 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: Sibling oocytes were allocated to Global ® or SAGE ® media system based upon laterality of ovary from which they were retrieved. All embryos were cultured in a time-lapse incubator. Blastocysts underwent trophectoderm biopsy for preimplantation genetic testing for aneuploidy using next-generation sequencing. MAIN RESULTS AND THE ROLE OF CHANCE: One hundred twenty-seven subjects (n = 127) had paired blastocysts for biopsy in each culture media system. There was no difference in top quality blastocyst formation (47.1 ± 31.0 vs 48.1 ± 27.2%; P = 0.87) nor aneuploidy rate (62.3 ± 34.0 vs 56.1 ± 34.4%; P = 0.07) for sibling embryos cultured in Global versus SAGE media system. Embryo morphokinetic parameters including time to each cell division from two cells (t2) to eight cells (t8), time to morula stage (tM), time to blastocele formation (tSB), time to fully formed blastocyst (tB) and time to expansion of the blastocyst (tEB) were similar between paired blastocysts from each culture media system. LIMITATIONS, REASONS FOR CAUTION: Pregnancy outcomes and offspring health data were not available for analysis. WIDER IMPLICATIONS OF THE FINDINGS: Commercially available culture media may not have a differential impact on embryo development and blastocyst aneuploidy rate when patient and stimulation-related factors are held constant. STUDY FUNDING/COMPETING INTEREST(s): There was no external funding for this study. C.H. is owner of a consultancy company, IVF Professionals, Chief Scientific Officer at Apricity, Executive Director at TMRW and co-owner and shareholder of Aria Fertility. She has received speaker fees, consulting fees and travel support from Cooper Surgical and Vitrolife. J.B. is an employee and shareholder of vitrolife. TRIAL REGISTRATION NUMBER: N/A.